1996
DOI: 10.1029/96gl02519
|View full text |Cite
|
Sign up to set email alerts
|

Seismic anisotropy beneath the Northern Apennines (Italy) and its tectonic implications

Abstract: We examined shear wave splitting in SKS and S phases from 22 teleseisms at 10 temporary stations on a transect across the Northern Apenninic arc. The array, near 43°N, spans from Corsica Island across the Tyrrhenian region and the Apenninic belt to the Adriatic coast. We applied particle motion, covariance matrix decomposition, and cross correlation methods to estimate the polarization direction of the fast split‐shear wave (ϕ) and the delay time between split phases (δt). Most of the analyzed shear waves show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
49
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 14 publications
(3 reference statements)
4
49
0
1
Order By: Relevance
“…An alternate hypothesis is that the rotation is associated with complicated flow patterns in the upper mantle, perhaps associated with the kink in the Pacific slab beneath Hokkaido and associated with the confluence of the Pacific and Philippine slabs beneath southern Kyushu. Without further modeling we cannot distinguish between these two hypotheses but we note that the rotation from trenchparallel fast directions close to the trench to trenchperpendicular away from the trench that we observe in our F-net dataset has been observed in other subduction systems (e.g., Smith et al, 2001;Margheriti et al, 1996;Nakajima and Hasegawa, 2004), although the opposite trend has also been observed (Levin et al, 2004).…”
Section: Interpretation Of F-net Splitting In Terms Of Tectonic Featuresmentioning
confidence: 50%
“…An alternate hypothesis is that the rotation is associated with complicated flow patterns in the upper mantle, perhaps associated with the kink in the Pacific slab beneath Hokkaido and associated with the confluence of the Pacific and Philippine slabs beneath southern Kyushu. Without further modeling we cannot distinguish between these two hypotheses but we note that the rotation from trenchparallel fast directions close to the trench to trenchperpendicular away from the trench that we observe in our F-net dataset has been observed in other subduction systems (e.g., Smith et al, 2001;Margheriti et al, 1996;Nakajima and Hasegawa, 2004), although the opposite trend has also been observed (Levin et al, 2004).…”
Section: Interpretation Of F-net Splitting In Terms Of Tectonic Featuresmentioning
confidence: 50%
“…Silver, 1994 and below the Tyrrhenian back-arc Ž . basin Margheriti et al, 1996 could provide evidences for a relative E-ward mantle flow. The mantle polarization would be able to differentiate the opposite behavior of the decollement planes along the W-directed and E-or NE-directed subduction zones and to determine the differences on the orogenic Ž .…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with a preferred orientation of the a-axis of olivine parallel to the fault direction (i.e., the shear direction), a situation expected for strike-slip faults in the mantle. Shear wave splitting measurements in Corsica (Margheriti et al, 1996) also hint to a coherent deformation of the crust and the mantle, associated to obduction during Alpine collision; in this case, the fast shear wave is polarized in a direction normal to the trend of the belt, i.e., parallel to the direction of thrusting. The measured delay time between the fast and slow split shear waves for all these examples implies that the lithosphere is affected by the fault-related fabric over its entire thickness.…”
Section: Rheology Of the Lithospherementioning
confidence: 99%